The adaptation of value at risk-adjusted sharpe model in measuring performance of Islamic Equity unit trust funds in Kuala Lumpur Stock Exchange (KLSE): some evidence / Nurul Aziera Saim, Siti Nurul Ain Alwi and Sharifah Izzatul Farhanah Syed Putera - Saim, Nurul Aziera; Alwi, Siti Nurul Ain; Syed Putera, Sharifah Izzatul Farhanah (2019)
Islamic unit trust fund in Malaysia has been one of the fastest-growing sectors within the finance industry over the last decades to fulfil the demand from Muslim investors. Muslim investors are only willing to invest their capital if the investment does not conflict with their religious beliefs, namely Islam. There are various types of Islamic fund available in Malaysia which are bond fund, balance fund, fixed income fund as well as equity fund. However, this study focuses on equity fund for investment. Previously, a set of traditional. performance measures suggested by Sharpe, Treynor and Jensen's Alpha used beta (systematic risk) or standard deviation (total risk) as their risk variable. In the present study, a performance measurement technique that consider only negative volatility (downside risk) such as Value at Risk (VaR) is proposed. Thus, the main objectives of this study are to measure the performance of five selected CIMB Islamic equity funds from 2016 to 2019 using Sharpe, Treynor, Jensen's Alpha and VaR-Adjusted Sharpe. Eventually, this study also aim to rank the performance of the selected Islamic unit trust funds against Kuala Lumpur Composite Index (KLCI) as the benchmark. Overall, the findings show that CIMB Islamic equity funds underperform the market index, KLCI. Result also show that the ranking using VaR-Adjusted Sharpe are similar to Treynor and Jensen's Alpha compared to the traditional Sharpe ratio. Hence, Value at Risk has been proved to successfully been adapted into Sharpe to evaluate the performance of unit trust funds and all measure successfully have been used. Therefore, this study can be used as a guideline in terms of financial performances as well as beneficial to local Muslim investors in risk management and portfolio optimization.